2020
DOI: 10.3390/mi11100886
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Flow through Microchannels for Inertia-Based Sorting: Steps toward Microfluidic Medical Devices

Abstract: The development of new standardized test methods would allow for the consistent evaluation of microfluidic medical devices and enable high-quality products to reach the market faster. A comprehensive flow characterization study was conducted to identify regulatory knowledge gaps using a generic inertia-based spiral channel model for particle sorting and facilitate standards development in the microfluidics community. Testing was performed using 2–20 µm rigid particles to represent blood elements and flow rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…With proper calibration, outputs like pressure or flow rate data can be used as indicators for the system performance. For example, previous research [ 70 ] has indicated that monitoring fluctuations in pressure may be an effective tool for optimizing performance of a microfluidic system. Overall, standardization efforts for flow-related testing will be useful for the microfluidic device community.…”
Section: Discussionmentioning
confidence: 99%
“…With proper calibration, outputs like pressure or flow rate data can be used as indicators for the system performance. For example, previous research [ 70 ] has indicated that monitoring fluctuations in pressure may be an effective tool for optimizing performance of a microfluidic system. Overall, standardization efforts for flow-related testing will be useful for the microfluidic device community.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing integration of microfluidics in environmental devices, there is a lack of specific EPA/WHOrecognized standards for microfluidic-based environmental monitoring, which poses a significant obstacle to device development and approval. 329 Standardized regulatory guidance documents regarding performance, sample integrity, interference mitigation, and calibration procedures are necessary to ensure accuracy, reliability, and user safety in environmental monitoring applications. In 2022, the Food and Drug Administration's Center for Devices and Radiological Health took a significant step forward in regulating microfluidics-based medical devices by developing a new leakage testing tool.…”
Section: Commercializationmentioning
confidence: 99%
“…Unfortunately, there is a lack of specific FDA standards tailored for microfluidics, necessitating manufacturers to either adapt existing standards or devise novel methodologies to demonstrate performance and secure patentability. As commercialization continues to grow, governmental organizations should develop more standards and quality assurance for innovators seeking to develop marketable microfluidic products 100 …”
Section: Applications For Food Safetymentioning
confidence: 99%